Exploring the Influence of Learning Styles on the Development of Critical Thinking Skills in Mathematics - Endang Yuliani; Ummi Rosyidah; Irma Ayuwanti; Iskandar (Journal of Transdisiplinary Studies in Education, 2025)
Background: Critical thinking in mathematics is a vital skill for solving complex problems. However, students' ability to think critically in mathematics varies according to their learning styles. This study investigates how auditory, visual, and kinesthetic learning styles influence students' critical thinking abilities in mathematical contexts. Aims: The goal of this research is to explore how different learning styles affect the development of critical thinking skills in mathematics and to determine how these styles influence students' performance in tasks requiring mathematical reasoning. Methods: A descriptive qualitative research design was used. The participants were middle school students selected using purposive sampling. Data collection involved critical thinking tests, learning style surveys, and interviews. The collected data were analyzed through presentation, reduction, and conclusion drawing, with triangulation employed to ensure data reliability. Results: The results revealed that students with visual learning styles showed the highest level of mathematical critical thinking, particularly in evaluation, analysis, interpretation, and inference. Auditory learners performed reasonably well in evaluation and analysis but faced challenges with interpretation. Kinesthetic learners demonstrated potential but required further improvement in analysis and evaluation. Conclusion: The study concluded that learning styles have a significant impact on the development of mathematical critical thinking skills. Visual learners performed the best, while auditory and kinesthetic learners exhibited potential but need additional support to enhance their abilities in critical thinking tasks. The findings highlight the importance of incorporating diverse teaching strategies that cater to various learning styles.